2020
DOI: 10.1177/0272989x20936272
|View full text |Cite
|
Sign up to set email alerts
|

Direct-Observation Cohort Study of Shared Decision Making in a Primary Care Clinic

Abstract: Background. Observational studies suggest that shared medical decision making (SMDM) is suboptimal. Our objective was to assess patient preferences, ratings, and objective measurements of decision making and their impact on patient outcomes. Methods. Hypertensive adults presenting for routine care with their primary care physician completed previsit surveys assessing SMDM preferences. Postvisit surveys assessed the degree of SMDM during the encounter, patient satisfaction, and trust. Encounters were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…It has been reported that, compared to OPTION-5, patients may unconsciously overestimate the occurrence of shared decision making by integrating in their evaluation prior visits or the relation with the clinician. 12,29 This is also plausible for RCVC-patient.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…It has been reported that, compared to OPTION-5, patients may unconsciously overestimate the occurrence of shared decision making by integrating in their evaluation prior visits or the relation with the clinician. 12,29 This is also plausible for RCVC-patient.…”
Section: Discussionmentioning
confidence: 82%
“…This implies that, when it comes to medical decisions requiring some amount of time and several patient-clinician encounters, using a single consultation to rate shared decision making may lead to an underestimation of the occurrence and the quality of the decision making process by observers compared to the patient's point of view. This may partly explain why patients' ratings of shared decision making tend to be higher than those of health professionals 12,32,36 and observers. 33,37,38 In addition, our measurements of SDM encompass different aspects of the SDM process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The previous literature comparing clinicians’ self-reported and actual decision-making style in medical consultations also showed that clinicians tend to overestimate the extent to which they apply SDM. 20 25 These studies analysed simple decisions in primary care such as refills and routine testing 20 or were performed in specific breast cancer or renal failure clinics in which the staff had been extensively trained in the application of SDM. 25 …”
Section: Discussionmentioning
confidence: 99%
“…Finally, like in earlier studies using the OPTION 5 instrument, our study focused on clinician behaviour and not on not on patients’ experiences. Given the scant literature on the topic, 20 28 29 more studies are needed to assess how patients experience the decision-making process in medical consultations…”
Section: Discussionmentioning
confidence: 99%